임산부의 철분 섭취량과 흡수율 및 관련된 영양지식에 관한 연구 ( Assessment of the Intake and Availability of Dietary Iron and Nutrition Knowledge in Pregnant Women ) - 김은경; 이규희 (대한지역사회영양학회지, 1998)
This study was designed to estimate mean daily iron intake and its bioavailabi- lity and to assess nutrition knowledge for 144 pregnant women in the last trimester. Serum ferritin concentration was analyzed to estimate their iron stores. Dietary intakes of iron(heme iron and nonheme iron), the amounts of MPF(meat, poultry and fish) and ascorbic acid were assessed by modified 24-hr recall method. The food frequency questionnaire was used to assess subjects usual food consumption patterns. The mean value of serum ferritin was $21.3±{15.2ng/ml}$ and 26.4% of the pregnant women had a serum ferritin level <12ng/ml(i.e. depleted iron stores). The mean daily intake of total orin in the pregnant women was 56.5%(17.0mg) of RDA and heme iron intake was 0.94mg which was 5.5% of total iron intake. Total absorbable iron calculated by the method of Monsen was 2.41mg and bioavailability of dietary iron was 2.41%. Food frequency test score of meats group was positively correlated(r=0.443) with the bioaavailability of dietary iron. The mean score on the nutrition knowledge test of subjects was 12.76(out of a possible 20 points). These results indicate that the nutritional iron status may be improved by increasing either the amount of iron in the diet or its availability.